2022
DOI: 10.1111/1467-8268.12621
|View full text |Cite
|
Sign up to set email alerts
|

Does aid matter for FDI in ECOWAS: Investigating the infrastructure channel

Abstract: This paper investigates whether and how aid targeted at specific subcategories of economic infrastructure could assist the economies of 14 Economic Community of West African States to attract higher foreign direct investment (FDI) inflow via improvement in infrastructure in water supply and sanitation, energy, transport and ICT. By relying on the three stage least squares estimation technique that is able to account for endogeneity among structural equations, and utilizing data spanning 2005-2018, we found qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Donaubauer et al (2016) suggest that aid in infrastructure improves the endowment in transportation, communication, energy and finance which, in turn, attracts a higher flow of FDI. Meanwhile, Onye et al (2022) conducted a study for a sample of 14 Economic Community of West African States and found that aid contributes positively to water supply and sanitation, energy, transport and Information and Communication Technology (ICT). However, the transmission effect through infrastructure seems unnecessary as foreign aid might have a direct and positive effect on FDI.…”
Section: Foreign Direct Investment and Foreign Aidmentioning
confidence: 99%
“…Donaubauer et al (2016) suggest that aid in infrastructure improves the endowment in transportation, communication, energy and finance which, in turn, attracts a higher flow of FDI. Meanwhile, Onye et al (2022) conducted a study for a sample of 14 Economic Community of West African States and found that aid contributes positively to water supply and sanitation, energy, transport and Information and Communication Technology (ICT). However, the transmission effect through infrastructure seems unnecessary as foreign aid might have a direct and positive effect on FDI.…”
Section: Foreign Direct Investment and Foreign Aidmentioning
confidence: 99%
“…The Organisation for Economic Co‐operation and Development (2008) notes the relevance of FDI to many economies. Even though some studies have found that FDI may be affected by economic uncertainties (Asamoah et al, 2022; Moraghen et al, 2021), Onye et al (2022) and Levchenko and Paolo (2007) suggest that flows of such nature help economies avoid the uncertainties associated with dependence on short‐term flows for investment and growth.…”
Section: Introductionmentioning
confidence: 99%